Effectiveness of Wireless Network Roaming Access Point using PEAP Security System to Improve Internet Access - Nugroho Saputra; Ivan Hanafi; Soeprijanto Soeprijanto; Jarudin Jarudin (Institut Teknologi dan Bisnis Bina Sarana Global, 2022)
Network security was an access prevention measure taken by the network administrator to limit things that were not permitted and were dangerous to threaten the local network. This was done to keep the network working correctly, and there was no threat from anywhere. The research objective was to determine the effectiveness of wireless access point roaming networks with 802.1x security systems in increasing Internet access. The sample number in the study was 40 respondents, with details of 20 respondents from lecturers and 20 respondents from employees at university. The sampling technique was stratified random sampling by classifying the population into two strata. This study's data collection techniques were observation, interviews, and questionnaires. The method used was a mixed-method approach. The subjective test results show that the user interface of the Test ver1.0 hotspot could provide the best experience for users. The effectiveness of an Access Point roaming wireless network with an 802.1x security system as measured on the satisfaction aspect gets an average System Usability Scale score of 81.38, meaning that it could meet the satisfaction aspect and was accepted for use by users.